A Study on Interning in the Digital Marketing Agency - Gupta, Abhishek (ATLAS SkillTech University, 2025)
The digital marketing industry has undergone a transformative evolution over the past decade, driven by the rapid advancement of technology and the increasing reliance on digital channels for business communication and consumer engagement. As of 2023, the global digital marketing market was valued at approximately USD 780 billion and is projected to grow at a compound annual growth rate (CAGR) of around 11.1% through 2030, reaching an estimated USD 1.1 trillion by the end of the forecast period. This growth trajectory is fueled by several key factors that are reshaping the landscape of digital marketing.
Project Report on A Study on Interning in the Digital Marketing Agency (2023-2025) Under the Guidance of Prof. Tapish Panwar
Keywords: digital marketing; marketing